IMPROVING THE COMPETENCE OF GRADE 9 STUDENTS ON THE CONCEPT OF DEMAND THROUGH SIM-BAHAN - PASCUA, JAYLORD (International Journal of Arts, Sciences and Education, 2024)
Learners have had difficulty in grasping necessary knowledge regarding the concept of demand in conventional way of teaching. Thus, this study aimed to assess the effectiveness of Strategic Intervention Material (SIM) with Barkada sa Tahanan in improving on one of the least mastered competencies of Grade 9 students’ which on the concept of demand. Strategic Intervention Material, a teacher-made tool, was employed to supplement regular teaching and enhance competency-based skills. Buddy system was employed to make the learning more engaging and fun. A True Experimental design was utilized, involving two groups to establish causality. The experimental group which composed of 40 students from Grade 9 Love, experienced the intervention, while the control group which consisted of 39 students from Grade 9 Charity where in it followed conventional way of teaching. Participants were enrolled in Claveria Rural and Vocational School during School Year 2022-2023.Various analyses were used, including Mean and standard deviation to gauge pretest and posttest scores of both groups, T-test to identify significant differences, Independent Sample T-test to compare control and experimental groups, and Paired Sample t-test to assess changes within the experimental group. Cohen’s D measured the impact of Strategic Intervention Material with peer tutoring on the concept of demand. Results indicated notable enhancement in Grade 9 learners’ competence after utilizing the intervention. Statistical analyses confirmed significant differences between pretest and posttest scores. The intervention demonstrated a substantial effect size on learners’ competence. Recommendations include devising action plans to sustain Strategic Intervention Materials’ development and usage. Furthermore, Araling Panlipunan teachers, particularly Economics teachers, are encouraged to adopt and disseminate the approach for broader implementation.